”Benchmarking As Approach For Development The Institutional Performance in Public Organization “Proposed Vision - Hassanein, Abdel Rahim Mohamed Abdel Rahim (Journal of Economic, Administrative and Legal Sciences, 2018)
The benchmarking is a strong approach for developing and improving the performance in the organizations, because it focus on compare the organization to be developed with the best practice in another organization or the organizational unit. The importance of this research concentrated in identify the importance results that the public organizations can gain as a result for applying the benchmarking and illustrate the steps that the organization must follow it to apply the benchmarking. To achieve research objectives, the descriptive analysis approach was used to analysis the previous studies and literature in benchmarking filed to formulate proposed vision. The research reached to many results one of them applying the benchmarking in public organizations helping in improve the performance, also the benchmarking helping to change the organizational culture in public organizations from a culture of information confidentiality to a culture of information dissemination. The research recommended to applying the proposed vision that mentioned in this research under title “proposed vision to applying the benchmarking as approach to develop the performance in public organizations.